The effect of nitric acid - hydrofluoric acid etching solution on the shear bond strength and mode of failure of resin cement to zirconia (In vitro study) - Farah I. Tahan; Ahmad M. Abdelhamid; Essam Osman; Ryan Harouny; Roula Hachem; Yaser M. Aly (Publymed, 2024)
The aim of this study is to determine the effect of an etching material which is the compound of nitric acid-hydrofluoric acid as a pretreatment agent on the shear bond strength of resin cement to two different types of zirconia and comparing it with air particle abrasion. 52 CAD/CAM Zirconia disks were prepared into 3D cubes of 8×8mm and thickness of 3mm. 26 of them were fabricated from high translucent white zirconia 'group I' and the other 26 from natural 3D multilayer monolithic zirconia 'group II'. Each group is then divided into subgroup A and subgroup B according to the surface treatment. All Zirconia cubes were bounded to resin cubes 6x6 mm. 13 of the cubes in subgroup A were treated with the etching material (the test group) and the other 13 in subgroup B were treated with air abrasion (control group). All samples were subjected to thermocycling. Shear bond strength and failure mode were evaluated. The data was collected, tabulated and statistically analyzed using Statistical Package for Social Sciences (SPSS) version 26. The results of the independents samples t-test revealed that there is a statistically significant difference between the shear bond strength in Etched and Air Abrasion in the High Translucent White Zirconia and that there is a statistically significant difference between the shear bond strength of etched and air abrasion in the 3D Multilayered Zirconia. However, there was no statistically significant difference between the shear bond strength among the two types of zirconia after air abrasion and after etching. Regarding the failure mode, it was revealed that most of the specimens that were etched in both types of zirconia have cohesive failure, while the majority of the specimens after air abrasion in both types of zirconia have adhesive failure. Zircos-E etching solution significantly improved bonding to zirconia, increasing shear bond strength with resin cement. Air abrasion on zirconia types resulted in low shear bond strength, indicating a weaker surface treatment compared to Zircos-E etching solution..